A transition program to adult health services for teenagers receiving long‐term home mechanical ventilation: A longitudinal qualitative study. Issue 3 (23rd January 2020) - Dale, Craig M.; Carbone, Sarah; Amin, Reshma; Amaria, Khushnuma; Varadi, Robert; Goldstein, Roger S.; Rose, Louise
Abstract: Objective: Adolescents receiving long‐term home mechanical ventilation (HMV) who survive into adulthood must transition to adult health care services. Lack of transition readiness is reported to result in poor health outcomes. The objective of this study is to explore longitudinally the pediatric‐to‐adult health care transition experience involving a transition program for adolescents receiving HMV including transition readiness, barriers, facilitators, and modifiable features. Design: A prospective qualitative longitudinal interview study of adolescent and family caregiver dyads recruited through a pediatric‐to‐adult HMV transition program jointly established by two collaborating health centers: The Hospital for Sick Children and West Park Healthcare Centre in Toronto, Canada. Eligible dyads were interviewed at three time points: pretransition, transition, and 12‐months posttransition. Interviews were transcribed verbatim and analyzed using directed content analysis methods. Results: Ventilator‐assisted adolescents (VAAs) and caregiver participants perceived a lack of transition readiness in their ability to manage health communication and coordination across multiple adult providers. Transition facilitators included early transition discussion, opportunities for VAAs to speak directly with HMV providers during appointments, receipt of print informational materials regarding adult services, and a joint pediatric‐adult team handover meeting. Modifiable transition barriers included lack of other specialist referrals, insufficient information about adult homecare service funding, and limited involvement of family doctors. Unresolved transition barriers resulted in perceptions of service fragmentation. Conclusions: Although the pediatric‐to‐adult HMV transition program conferred benefits service fragmentation was perceived. Transition barriers may be overcome through early planning and staged transition with all specialists, community providers, and the family and adolescent working in collaboration.